The Application of Job Sheet Teaching Material Products on Project-Based Learning at Vocational School Mikael Surakarta - Triyanto, Triyanto; Parno, Parno; Sukatiman, Sukatiman (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This study explores the role of teaching material products and job sheets in the implementation of project-based learning at SMK Mikael Surakarta. This type of research is qualitative research with a case study method. Data collection techniques through observation, documentation, and interviews. The research design uses an ethnographic design. Informants as resource persons were vice principals in the field of curriculum, heads of machining engineering competency skills, heads of production units, and teachers of machining engineering practice. The data that has been collected is then analyzed through data reduction, data presentation, and conclusion. Validity testing uses source triangulation and technique triangulation. This research shows that schools can fulfill the procurement of equipment and materials in stages. Based on the findings, learning tools provide support for project-based learning in the form of (1) preparing job sheet documents as a learning tool for students during practice. The job sheet is in the form of material stages to achieve student competency targets. (2) ensure that the results of objects that students work on through the competency stages can be used as products with use value.